Penerapan Analisis SWOT dalam Meningkatkan Penjualan pada Restoran “Ayam Goreng Ananda” Jember - Sirmadani, Trisna Bela; Nurhasanah, Elsa Weres; Arifah, Naili Nur; Fuadah, Lina; Qomariah, Nurul (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The increasingly fierce level of business competition currently means that business actors need to have a strategy in order to survive and develop. Companies and MSMEs need to implement effective marketing strategies to increase sales to prepare themselves to face increasingly fierce competition from other competing businesses. By using a SWOT analysis, a business can determine what needs to be improved both internally and externally to ensure work operations run smoothly. This research aims to see the application of SWOT analysis to the factors that influence sales and to analyze the application of SWOT analysis in increasing sales volume at the